An Evaluation of the Implementation of Electronic Medical Records on Healthcare Service Performance Using SEM-PLS - Arie Gunawan; Asrul Sani; Harun Al Fathih Gunawan (Scientific Journal of Informatics, 2026)
Purpose: The study aims to explore the factors that determine the successful implementation of Electronic Medical Records in community health centers of Indonesia in which System Quality, Information Quality, and Perceived Ease of Use are proposed to influence User Satisfaction, and then the impact of User Satisfaction on Healthcare Service Performance is measured. Methods: A quantitative cross-sectional survey was conducted involving 180 healthcare professionals, namely physicians, nurses, administrative staff, and information system operators who routinely use EMR systems. The data were collected through a five-point Likert-scale questionnaire. The proposed model is the DeLone and McLean Information Systems Success Model and Technology Acceptance Model (TAM) integrated. Data analysis was performed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS 4. Result: The results show that System Quality, Information Quality, and Perceived Ease of Use significantly and positively affect User Satisfaction, which then significantly positively influences Healthcare Service Performance. The results further show that User Satisfaction mediates the relationship between technical system characteristics and organizational performance, highlighting the importance of system reliability, information quality, and usability for improved delivery of healthcare services. Novelty: This paper presents an SEM-PLS model that integrates the DeLone and McLean Information Systems Success Model with TAM in explaining healthcare service performance through User Satisfaction. The proposed framework not only offers a holistic approach to evaluate EMR implementation but also provides practical insight to enable the sustainability of digital health transformation in Indonesian community health centers.